Unicornuate Uterus with Rudimentary Horn and Complicated with Endometriosis: Uterus Unikornuasi dengan Kornu Rudimenter dan Endometriosis - Liva Wijaya; Junizaf Junizaf; Shirley Anggraini; Djoni Nurung; Prijono Prijono; Punarbawa Punarbawa (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To report the congenital abnormalities of müllerian duct and review its literature. Methods: Case report. Case: A sixteen years old unmarried woman came to our policlinic with chief complain of cyclical abdominal pain (VAS 6). She had regular menstruation. In other hospital, she had diagnosed as suffering from ovarian tumor. Our examination showed that the uterus was unicornuate with rudimentary horn. We did explorative laparotomy. We took out the left cornu and left salpingoophorectomy due to hematosalphing and endometrial cyst. The Visual analogue score after surgery was reduced until VAS 2. Conclusion: Congenital abnormalities of the müllerian ducts are relatively common. Comprehensive examination can diagnose this abnormality earlier, thus intervention can be given as soon as possible. Keywords: abnormalities müllerian ductus, endometriosis